(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Online shopping or known as e-shopping is one of the forms of electronic commerce which allows consumers to purchase goods or services from a seller over the internet using a web browser without going to the shop itself. Alternative names for online shopping are e-web-store, e-shop, e- store, and internet. Online shopping has given all types of consumers the ability of being able to buy anything, anywhere, and any product, regardless of where its location is in any part of the world .it involves various factors like, low price, saves time, convenience, all time shopping accessibility, broad availability of products but involves the risk of personal privacy and transactional security. Online shopping offers a tremendously different shopping experience for people in developing nations like India. Convenience is one of the main reasons for going into online shopping. Large discounts and offers provided by the online sellers also appeal to numerous buyers. This study tries to discover the customer preference towards online shopping.